Studi Literatur: Meningkatkan Kemampuan Membaca Anak SD Melalui Buku Cerita Bergambar - Kasanah, Silfiana Putri Uswatun; Mukhlis, Karina Radan; Fidha, Aima Zahro (Lembaga Intelektual Muda (LIM) Maluku, 2024)
The aim of this research is to describe improving reading ability through picture story books. The research method uses the literary study method. Where the data collection system in this research comes from books or journals which are analyzed based on existing problems. The results of this research indicate that picture story books are effective in improving students' reading skills. This is possible because when reading story books students are very motivated, because story books are a favorite among students in general. So, when the lesson material is changed into the form of a picture story, it really attracts students' attention